LEGAL FORCE IN UNCERTIFIED LAND OWNERSHIP: KEKUATAN HUKUM DALAM KEPEMILIKKAN TANAH YANG TIDAK BERSERTIKAT - Lafau, Kasiria (LPPM UPMI, 2023)
The purpose of this research is to find out how the application of the law on the transfer of land rights without a certificate according to Article 1963 of the Civil Code and how land rights are according to the expiration in Article 1963 of the Civil Code. Land rights without certificates according to expiration in Article 1963 of the Civil Code, states that a land that has been occupied by someone without a certificate as strong evidence, can obtain ownership rights to the land due to expiration or the passage of time. Where the person has cultivated, managed, and utilized the land properly within twenty to thirty years.